2021
DOI: 10.32479/ijeep.10991
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Nature of Energy Management and Responses to Policies Regarding Solar and Wind Pricing: A Qualitative Study of the Australian Electricity Markets

Abstract: The present study employed various qualitative techniques to investigate the nature and influence of policies and regulations concerning solar and wind pricing on the Australian electricity spot and options markets. The analysis was based on data gathered through interviews conducted with energy managers, chief executive officers and other significant personnel from the Australian electricity industry. The interviewees' responses regarding the solar and wind policies of relevance to the Australian electricity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In the region of African continent, Nathaniel et al (2021) has found an impact of energy consumption, natural resources, and urbanization on ecological footprint in South Africa, whereas human capital plays a role in improving the environment. Alsaedi et al (2021) explored the Australian electricity markets by examining the energy management nature of policies and framework on solar and wind pricing. In their analysis, such policies can lower the price of electricity and minimize some risks for investors at the same time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the region of African continent, Nathaniel et al (2021) has found an impact of energy consumption, natural resources, and urbanization on ecological footprint in South Africa, whereas human capital plays a role in improving the environment. Alsaedi et al (2021) explored the Australian electricity markets by examining the energy management nature of policies and framework on solar and wind pricing. In their analysis, such policies can lower the price of electricity and minimize some risks for investors at the same time.…”
Section: Literature Reviewmentioning
confidence: 99%